Opening and Closing the Future: Climate Change, Adaptation, and Scenario Planning. (August 2014) - Rickards, Lauren; Ison, Ray; Fünfgeld, Hartmut; Wiseman, John
The gales of climate change blow the future open and closed. In response, we are having to learn to live with a renewed notion of limits and a novel level of uncertainty. One emerging governance response is a turn to scenario planning, which generates narratives about multiple futures refracted out from the present. Like climate change itself, scenario planning, and the broader field of futures studies it is part of, is historically and socially positioned, belying its application as a mere method or tool. This paper discusses the growing turn to scenario planning within government climate change adaptation initiatives in light of parallel shifts in governance (eg, interest in efficiency and wicked problems) and adaptation efforts (eg, framed as risk management or resilience) and their shared roots in the ambiguities of sustainable development. It provides an extended introduction to a theme issue that provides, overall, a nested discussion of the role of scenario planning by government for climate change adaptation, noting how governance, climate change adaptation, and scenario planning all fold together the motifs of openness and closedness. This paper engages with the emerging field of future geographies and critical interest in future orientations to highlight the way society's growing engagement on climate change adaptation exposes, critiques, replicates, and amplifies our existing orientations to the future and time and their politically contested and embedded character. It points to the way the motif of open futures can be both progressive and conservative, as political and economic interests seek to open up some futures while closing down others in the name of the ambivalent goals of adaptation and sustainable development.